(untitled) (Balneo and PRM Research Journal, 2024)
Abstract Introduction: It is well known that cardiovascular diseases are the leading cause of death worldwide. In Romania in 2015, cardiovascular diseases led to 153.953 deaths, representing 59.3% of deaths from all causes. Most people in Romania today have an unhealthy lifestyle, characterised mainly by a poor nutritious diet, low physical activity and a lack of medical screening. Purpose: Considering these deficits of secondary prevention in the treatment line of the Romanian cardiovascular patient, we aimed through this study to assess the current access of the Romanian population to on-site and remote cardiac rehabilitation programs as well as their opinion regarding the telemedicine for future cardiovascular care modelling.